2022
DOI: 10.21037/apm-21-213
|View full text |Cite
|
Sign up to set email alerts
|

HER2 exon 20 insertion mutations in lung adenocarcinoma with leptomeningeal metastasis: a case report and response to poziotinib

Abstract: Leptomeningeal metastasis (LM) is associated with poor prognosis and represents a terminal event of non-small cell lung cancers (NSCLC). In previous studies, most of LM-patients have detected epidermal growth factor receptor (EGFR) mutation and responded to the third generation of EGFR-tyrosine kinase inhibitor (TKI). This study aimed to report a case of ERBB2 (HER2) exon 20 insertion mutations in the cerebrospinal fluid (CSF) of LM-patient which response to poziotinib. At the beginning, postoperative patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In the present study, it is worth noting that different ERBB2 20ins subtypes was identified in patients between the two regions. TKIs targeting ERBB2 have limited activity in patients with ERBB2 -positive tumors [ 37 , 38 ], although some case series have reported that lung cancer patients with ERBB2 20ins can benefit from TKIs, such as afatinib [ 39 ] and poziotinib [ 40 ]. However, response heterogeneity was observed in patients harboring different 20ins subtypes [ 39 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it is worth noting that different ERBB2 20ins subtypes was identified in patients between the two regions. TKIs targeting ERBB2 have limited activity in patients with ERBB2 -positive tumors [ 37 , 38 ], although some case series have reported that lung cancer patients with ERBB2 20ins can benefit from TKIs, such as afatinib [ 39 ] and poziotinib [ 40 ]. However, response heterogeneity was observed in patients harboring different 20ins subtypes [ 39 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are relatively few reports of rare oncogenes, such as RET rearrangement or HER2 mutation causing LM. There is a case report 64 of lung adenocarcinoma accompanied by rare oncogene HER2 exon 20 insertion mutations that causes LM. After 3 days of administration of poziotinib, the symptoms improved significantly and the PFS was nearly 2 months.…”
Section: Treatment Of Nsclc-lmmentioning
confidence: 99%